Hybrid-Mode Impedance Control for Position/Force Tracking in Motor-System Rehabilitation. (24th June 2015) - Kim, Youngwoo
This paper proposes a new robot controller for motor-system rehabilitation. The proposed controller simultaneously realizes rehabilitation motion tracking and force generation, as predefined through a musculoskeletal model-based optimization process. We introduce control parameters of weighted control action priorities for the motion-tracking and force-generation tasks, based on the position-tracking error. With the weighted control action priorities, the robot accords higher priority to motion tracking at the robot end point when the position-tracking error is larger than a threshold value, and to force generation when the position-tracking error is smaller than a threshold value. Smooth motion trajectory has to be designed and applied in robot-based rehabilitation. Through simulations and experimental results, we show the usefulness of the proposed control method.